Decision making in emergency management. - Glarum, Jan (Elsevier Science & Technology, 2019)
Decision-Making in Emergency Management examines decisions the authors have made over their careers based on their combined training, experience and instinct. Through a broad range of case studies, readers discover how experience impacts decision-making in conjunction with research and tools available. While the use of science, data and industry standards are always the best option when it comes to handling emergency situations, not all emergency situations fit one known solution. This book comprehensively explores the question "Is 'instinct' a viable factor when faced with a challenging situation and how close does it match up with the best science available?"